1991
DOI: 10.1017/s0263574700010262
|View full text |Cite
|
Sign up to set email alerts
|

A Variational Approach for Modeling Flexibility Effects in Manipulator Arms

Abstract: SUMMARYThis paper presents a general technique to model flexible components (mainly links and joints flexibilities are considered) of manipulator arms based on Castigliano's theorem of least work. The robotic arms flexibility properties are derived and represented by the matrix of compliance coefficients. Such expressions can be used to determine the errors due to the robotic tip deformations under the application of a set of applied loads at the tip in a Cartesian space. Once these deformations are computed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Lagrangian dynamics has been utilized in conjunction with the assumed modes method to derive equations of motion. Meghdari [3] has presented a general technique to model flexible components of robotic arms based on Castigliano's theorem. The flexibility properties of the manipulator arms are derived and represented by a matrix of compliance coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Lagrangian dynamics has been utilized in conjunction with the assumed modes method to derive equations of motion. Meghdari [3] has presented a general technique to model flexible components of robotic arms based on Castigliano's theorem. The flexibility properties of the manipulator arms are derived and represented by a matrix of compliance coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical model will be derived using a variational method based on Castigliano's theorem of least work (CTLW) [6]. It will be shown that minimum two strain gages per link are needed to monitor deflections subjected to bending in a plane.…”
Section: An Iterative Methods Based On the 4*4 Transformation Matrix Imentioning
confidence: 99%
“…The axial deflection is cause by axial force Fa and it is described by axial displacement &a as shown in Figure 3. The magnitude of axial bending deflection is relatively small compared with the torsional and bending deflections in manipulator applications, hence the axial deflection is neglected in most of previous research [5,6,12]. Only the bending deflection in a plane is investigated in this project.…”
Section: Ii2 Links Under Payloadsmentioning
confidence: 99%
See 2 more Smart Citations